NON AGRICULTURAL USE OF SOIL: EARTH INK AS TECHNOLOGICAL AND SUSTAINABLE INNOVATION - Vital, A. F. M.; Cavalcante, F. L.; Araújo, J. M. M.; Barbosa, I. S.; Oliveira, D. S.; Azevedo, G. H. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The indiscriminate exploitation of natural resources directs the market to seek new technologies as a warning to the possible shortage of materials. In the context of construction, the use of new paint alternatives is an urgency and the use of earth-based paint is an innovative, economical and viable alternative, considering the socio-environmental appeal of the proposal. The objective of this work is to present the perception of farmers about the paint with earthen paint, such as social ecotechnology for the valorization of the non - agricultural potentials of the soil and the opportunity to generate work and income. The activities took place in a rural association in Cariri (PB). Initially a semi-structured questionnaire was applied to verify the participants’ understanding of the morphology and non-agricultural use of the soil. Then the painting workshop with earth (geotinta) was realized. The results show the absence of concepts about soil characteristics and their non - agricultural potential. After the workshop the perception of the farmers changed and these were enthusiastic about the paint of earth, as innovation for painting of the houses and as opportunity to add income by the craftsmanship. Geotint is evidenced as a possibility for dissemination of concepts on the soil, promotion of sustainable postures and ecotechnology for innovation.